(untitled) (Health and Biosciences, 2025)
Healthcare-associated infections (HAIs) remain a significant global health concern, contributing to increased morbidity, prolonged hospital stays, and rising healthcare costs. Adherence to infection prevention and control (IPC) practices by healthcare workers (HCWs) is critical to reducing these risks. To evaluate the knowledge, attitudes, and practices (KAP) of HCWs in the Western Region of Saudi Arabia regarding IPC. A cross-sectional survey was conducted among 780 HCWs, including physicians, nurses, pharmacists, and allied health staff from multiple hospital departments. Data were collected using a structured questionnaire assessing demographics, knowledge, attitudes, and practices toward IPC. Descriptive statistics and logistic regression analysis were performed to identify predictors of compliance. Most participants demonstrated good knowledge of hand hygiene (92%) and WHO IPC guidelines (88%), though gaps persisted in knowledge of sterilization protocols (68%). Attitudes were generally positive, with 88% identifying IPC as highly important and 84% emphasizing the role of leadership support. However, practices were inconsistent: 80% reported updating practices according to new IPC guidelines, only 56% conducted regular IPC assessments, and just 20% consistently reported non-compliance. Logistic regression analysis showed that availability of PPE (OR = 3.6), prior IPC training (OR = 2.0), confidence in applying IPC measures (OR = 2.5), and longer work experience (OR = 2.8) were significant predictors of adherence. HCWs in Western Saudi Arabia demonstrate strong knowledge and positive attitudes toward IPC but suboptimal compliance in practice. Continuous training, supportive leadership, and systematic institutional audits are essential to strengthen adherence and reduce the burden of HAIs.